The NMDA receptor regulates competition of epithelial cells in the Drosophila wing - Agnes R. Banreti (Nature Portfolio, 2020)
Cell competition among epithelial cells allows removal of unfit or dangerous cells. Here, the authors show that the NMDA receptor is an important determinant of cell fitness in the Drosophila wing, also in the context of Myc super-competitor cells, with “loser” cells contributing metabolitic fuel to “winner” cells.